Makna Teologis dan Signifikansi Misiologis Simbol Empat Injil dalamPelayanan Albert Benjamin Simpson - Atakameng, Merianti (PT. Giat Konseling Nusantara, 2025)
This article examines the theological meaning and missiological significance of the Fourfold Gospel symbols developed by Albert Benjamin Simpson—Jesus as Saviour, Sanctifier, Healer, and Coming King. Employing a literature-based approach and content analysis, this study explores the theological foundations of these symbols and their application within a holistic global mission framework. The findings indicate that the Fourfold Gospel is not merely a doctrinal formulation but a ministry paradigm that integrally addresses spiritual, social, and eschatological dimensions. Simpson’s thought proves to be highly relevant in responding to the contemporary multidimensional crises and offers a contextual and transformative model of proclamation. Accordingly, these symbols remain profoundly pertinent for today’s Church in cultivating ministries that empower both individuals and communities in a comprehensive manner.